Agricultural and industrial development in Taiwan - Yu-Kang, Mao; Schive, Chi (International Food Policy Research Institute, 1995)
Over the past four decades Taiwan's economy has experienced significant structural change. At the outset of this period, Taiwan was just recovering from the ravages of World War II, and the economy was heavily dominated by the agricultural sector, which accounted for one-third of the net domestic product, more than half (56 percent) of total employment, and 92 percent of total exports. By 1988 agriculture's share of the net domestic product (NDP) had dropped to 6 percent, its share of total employment was down to 13.7 percent, and the sector accounted for only 6.1 percent of the total exports, including processed foods. These were years of high and stable economic growth: the real gross national product (GNP) grew at an average rate of 8.8 percent from 1952 to 1989, and two oil crises of the 1970s seemed to have little negative impact.' Between 1952 and 1987, per capita GNP, at 1981 constant prices, increased more than seven times, for an annual increase of 6.2 percent. In view of this growth, Taiwan is likely to be classified as an industrial economy by the turn of the century (Klein 1986).